Standar Kompetensi Manajerial Pegawai Negeri Sipil Di Badan Pengembangan Sumber Daya Manusia Aceh (Studi Deskripsi Keterkaitan Kompetensi Manajerial Dan Kinerja Organisasi) - Raja Muda (Puslatbang KHAN, 2019)
This study aims to find the role of managerial competency in improving individual performance and ignition of organizational performance in The Aceh Human Resource Development Agency. The method is a descriptive research method that explain the phenomenon of research objects and compared to previous research and other scientific references. The managerial competencies discussed include integrity, communication, cooperation, public service orientation, self and others development, change management and decision making. The results show that managerial competencies aree not directly related to organizational performance, but has a direct effect on individual performance. The relationship between organizational performance and managerial competencies is mediated by individual performance. Accumulation of individual performance which later will directly influence the achievement of organizational performance. The results of the study also find that the standard managerial competency documents has not been prepared yet so that competency development efforts are not fully based on planning.